Demand Planning Information Sharing: N ZAR - Mtshali, Nontobeko Nontokozo; Mbhele, Thokozani Patmond; Neboh, Nkechi Dorothy (Journal of Reviews on Global Economics, 2019)
Organisations are currently faced with difficulties in effectively aligning demand plans to the volatile environments in which they operate. While operating environments and consumer needs change, capacity capabilities often do not reflect the demand plans. The absence of alignment results in inaccurate forecasts, thus putting the long-term sustainability of a business at risk. The focus and aim of the study is to understand how demand planning information are shared at N ZAR for optimal performance. A quantitative explorative case study research design is being used and data was collected through a structured self-administered questionnaire in this study. The sample size was 86, which comprised of employees from Demand and Supply Planning, Finance and Control, Sales and Marketing divisions. The sample includes top management, middle management, first level management and non-management. Data analysis uses descriptive and multivariate statistics. The study findings show most of the participants responded positively to the statements that information sharing achieves demand chain coordination. This study recommended that top management should provide full support to information sharing initiatives to facilitate the demand planning process.